STRATEGI PENCEGAHAN BULYING DI LINGKUP PESANTREN - Latifatu Sya’diyah; Revi Fradita; Siti Roudhotul Jannah (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2025)
Bullying is a problem that occurs not only in public schools but also in religious educational settings such as Islamic boarding schools (pesantren). This phenomenon is concerning because it contradicts the primary objective of pesantren education, which emphasises the cultivation of noble character. This article aims to identify and examine strategies for preventing bullying in pesantren through an Islamic values-based approach. The method used is a literature review with descriptive analysis. This research employs a descriptive qualitative approach with a literature review method. Data was obtained from various sources such as books, journals, and scientific articles discussing bullying and character education in the context of Islamic boarding schools. Analysis was conducted by examining and reviewing the content to formulate a synthesis of prevention strategies based on Islamic values. The results of the study indicate that bullying prevention can be achieved through three main approaches: strengthening Islamic character education, empowering students as agents of peace, and enhancing the role of kyai and ustadz in moral supervision and guidance. With the consistent implementation of these strategies, Islamic boarding schools are expected to create a safe, peaceful, and supportive environment for the development of noble character.